Dyspnea: An underestimated symptom in Parkinson's disease. (March 2019) - Baille, Guillaume; Chenivesse, Cécile; Perez, Thierry; Machuron, François; Dujardin, Kathy; Devos, David; Defebvre, Luc; Moreau, Caroline
Abstract: Introduction: Dyspnea is one of the least well-characterized non-motor symptoms (NMS) associated with Parkinson's disease (PD). Objective: To determine the frequency of dyspnea in a large, single-center cohort of consecutive PD patients with no history of lung or heart disease, and to compare clinical features in dyspneic vs. non-dyspneic patients. Methods: Patients with abnormal cardiovascular and pulmonary results in a clinical examination were excluded. A positive response to at least one question ("In the last month, have you suffered from breathlessness?" and "In the last month, have you had trouble breathing normally?") was considered to signify the experience of dyspnea. MDS-UPDRS, global cognitive performance, non-motor symptoms and quality of life were assessed. Results: In the cohort of 153 non-demented PD patients (mean age ± standard deviation: 63.9 ± 7.4; mean disease duration: 9.2 ± 6.1 years), the mean [95% confidence interval (CI)] frequency of dyspnea was 39.2% (31.5–47). After adjustment for disease severity, PD patients with dyspnea had a significantly higher Movement Disorders Society Unified Parkinson's Disease Rating Scale part I, II and IV scores, a higher HAD anxiety and depression scores and a significantly higher 8-item Parkinson's Disease Questionnaire. Conclusion: Dyspnea is a frequent NMS in PD. Its pathophysiology and prognostic value need more investigation. Highlights: Dyspnea is a frequent symptom in Parkinson's disease. It is related to disease severity. It is linked to non-motor aspects of Parkinson's disease notably to anxiety and depression.